FEATURES OF ALLOYED A MATRYX OF WATER-DISPERSED IRON POWDERS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2021)
The publication examines the peculiarities of alloying a matrix of water-dispersed iron powders of the type ASC 100.29, AHC 100.29 and ABC 100.30. The possible ways of alloying in powder metallurgy are presented. The influence of the main alloying elements - copper, nickel, phosphorus, molybdenum, etc. was traced. on the technological process in the production of powder metallurgical details. A special place is given to the alloying elements intensifying the process of coagulation of the pores in the matrix during sintering - copper and phosphorus. Graphical dependences for the influence of copper on the dimensional changes of the iron matrix at different sintering temperatures are presented.